Pemantauan Perubahan Total Suspended Solid di Sungai Mahakam Kota Samarinda Menggunakan Citra Satelit Sentinel-2 Tahun 2018, Tahun 2021, dan Tahun 2024 - Agustin, Sinthia Putri; Kurniadin, Nia; Pramono, Dwi Agung; Suryalfihra, Shabri Indra (Geomatics Technology Study Program, Politeknik Pertanian Negeri Samarinda, 2025)
This research is motivated by the importance of the Mahakam River as a vital source of livelihood and economic activity in the city of Samarinda, where water quality requires special attention. One of the key parameters in determining water quality is Total Suspended Solids (TSS), which indicates the amount of suspended particles in the water and affects both water clarity and aquatic ecosystems. Conventional water quality monitoring methods are often time-consuming and costly. Therefore, remote sensing technology using Sentinel-2 satellite imagery provides a more efficient alternative for monitoring TSS changes in the Mahakam River over time. Based on the analysis of Total Suspended Solids (TSS) using the Budhiman and Parwati algorithms in the Mahakam River, it was found that TSS values changed during the period from 2018 to 2024. In 2018, TSS values based on the Budhiman algorithm ranged from 101.4181 mg/L to 151.0301 mg/L, while the Parwati algorithm showed a range from 125.1161 mg/L to 221.8730 mg/L. The highest TSS level in 2018 was recorded at STA 06 according to both algorithms. In 2021, the highest TSS value based on the Budhiman algorithm reached 538.0830 mg/L at STA 17, while the Parwati algorithm recorded a peak of 897.9948 mg/L at STA 01. In 2024, the Budhiman algorithm noted a significantly high value of 227.9285 mg/L at STA 21, while the Parwati algorithm showed the highest value of 954.8387 mg/L at STA 04.